The Personalized Approach to the Chronic Central Serous Chorioretinopathy Treatment Based on the Navigated Micropulse Laser Technology - P. L. Volodin; A. V. Doga; E. V. Ivanova; V. A. Pismenskaya; Iu. I. Kukharskaya; E. S. Khrisanfova (Oftalʹmologiâ)
The Purpose — to develop the technology and to evaluate the clinical results of personalized laser treatment of patients with chronic central serous chorioretinopathy (CSC) in a micropulse mode with individual selection of energy parameters on the navigation system Navilas 577s. Patients and Methods. 19 patients (22 eyes) with CSC after micropulse laser treatment were analyzed. The initial best corrected visual acuity (BCVA) was 0.4 to 1.0. According to OCT, the height of the  detachment of the neurosensory retina varied from 83 to 259 microns. Retinal sensitivity of the central zone was from 20.2 to 29.7 dB. Before laser treatment were individually selected the optimal energy parameters for each patient. The treatment was performed on a Navilas 577s laser system. The follow-up were 1 and 3 months. Results. 1 month after treatment the positive dynamics of functional and anatomical results in all patients was observed. Mean BCVA increased in the group to 0.81 ± 0.04. The central retinal sensitivity raised on average in the group up to 25.7 ± 0.6 dB. After 3 months, mean BCVA was 0.96 ± 0.02. Mean central retinal sensitivity increased to 26.4 ± 0.57 dB. The study revealed a high correlation between visual acuity and the central retinal thickness (0.72) and medium correlation between foveal retinal sensitivity and central retinal thickness in fovea (0.60), respectively. The correlation among visual acuity, retinal sensitivity and the symptom’s duration of the disease is negative medium (-0.63) and significant (-0.72), respectively. Conclusions. The developed personalized technology of laser treatment of chronic central serous chorioretinopathy with a micropulse mode with an individual selection of energy parameters on the Navilas 577s navigation system showed high clinical efficiency and safety. It has been established that in the course of the longstanding duration of the disease irreversible changes in the chorioretinal complex structure occured, thinning of the foveal photoreceptors layer leading to a decrease in the central retinal sensitivity and visual acuity, which substantiate the necessity for early and maximally functional-saving treatment.